Herbivorous mammals adjust their feeding patterns according to the abundance of available diet to adapt to the effects of grassland degradation - Xin He; Yutong Liu; Siwei Yang; Guiwen He; Gang Liu; Junsong Zhao (Global Ecology and Conservation)
The degradation of grasslands on the Qinghai–Tibet Plateau has severely impacted the region’s ecology and productivity, subsequently affecting the dietary niche of the region’s herbivores. Currently, little is known about the dietary strategies of plateau pikas (Ochotona curzoniae), an important species in the Qinghai–Tibet Plateau ecosystem, or freely grazing yaks (Bos grunniens) in response to grassland degradation. Fecal samples from plateau pikas and yaks were collected from degraded grasslands in the southwestern part of the plateau. The feeding habits and interactions between plateau pikas and yaks were investigated using chloroplast trnL-P6 amplification and sequencing technology to determine how these have changed given different levels of grassland degradation. The results indicated that alterations in food resources due to grassland degradation led to significant differences in the proportions of shared food types consumed by yaks and pikas; hence, these species adjusted their dietary breadths to mitigate the adverse effects of grassland degradation. As grassland degradation intensified, the proportion of shared food types between yaks and plateau pikas increased, suggesting that grassland degradation may increase dietary competition between these two species.